The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1258/000456302760042182
|View full text |Cite
|
Sign up to set email alerts
|

Free cortisol index as a surrogate marker for serum free cortisol

Abstract: Free cortisol index is a reliable and user-friendly measure of serum free cortisol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
66
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(71 citation statements)
references
References 8 publications
2
66
0
1
Order By: Relevance
“…Total plasma cortisol is made up of both bound and free fractions, and free cortisol is the form that is active, because it crosses cell membranes and interacts with receptors. Therefore, measuring both plasma CBG levels and total plasma cortisol levels allows free plasma cortisol to be estimated, which is a better measure of cortisol activity than the measurement of total plasma cortisol alone (29). Our results indicated that both total cortisol and free cortisol levels were higher in the plasma of the patient group than in the plasma of the control group.…”
Section: Discussionmentioning
confidence: 65%
“…Total plasma cortisol is made up of both bound and free fractions, and free cortisol is the form that is active, because it crosses cell membranes and interacts with receptors. Therefore, measuring both plasma CBG levels and total plasma cortisol levels allows free plasma cortisol to be estimated, which is a better measure of cortisol activity than the measurement of total plasma cortisol alone (29). Our results indicated that both total cortisol and free cortisol levels were higher in the plasma of the patient group than in the plasma of the control group.…”
Section: Discussionmentioning
confidence: 65%
“…Foregoing studies can be criticized because of changes in binding proteins such as cortisol-binding globulin (CBG) and albumin, confounding estimation of biologically active free cortisol from total cortisol measurements and thereby assessment of adrenal function [1,4,5,[7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Indeed, low binding proteins may overestimate relative adrenal insufficiency assessed from (increases in) total cortisol.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies suggest that abnormalities in cortisol action and HPA axis control may be a factor that links disturbances of carbohydrate metabolism (which characterize insulin resistance) and obesity (5)(6). In obesity, estimation of plasma cortisol does not reflect the function of the HPA axis (7), and levels of cortisol in obese patients have been reported to be normal (8), low (9), or increased (10). On the contrary, response to different stimuli (high secretion of cortisol after laboratory stress tests or after different exogenous neuropeptides) has been found to be altered (11).…”
mentioning
confidence: 99%
“…Nevertheless, it has been widely used to evaluate the HPA axis in obesity, and the outcomes are contradictory (12)(13)(14). The free cortisol index (FCI)-the total cortisol-to-cortisolbinding globulin ratio (CBG) -has also been proposed to be able to evaluate HPA axis activity (7,15) since it reflects the biologically active fraction of total cortisol (7). Moreover, FCI is significantly associated with several features of insulin resistance syndrome (15).…”
mentioning
confidence: 99%